5(3x-1)+7=2-(5x-3)

Simple and best practice solution for 5(3x-1)+7=2-(5x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-1)+7=2-(5x-3) equation:


Simplifying
5(3x + -1) + 7 = 2 + -1(5x + -3)

Reorder the terms:
5(-1 + 3x) + 7 = 2 + -1(5x + -3)
(-1 * 5 + 3x * 5) + 7 = 2 + -1(5x + -3)
(-5 + 15x) + 7 = 2 + -1(5x + -3)

Reorder the terms:
-5 + 7 + 15x = 2 + -1(5x + -3)

Combine like terms: -5 + 7 = 2
2 + 15x = 2 + -1(5x + -3)

Reorder the terms:
2 + 15x = 2 + -1(-3 + 5x)
2 + 15x = 2 + (-3 * -1 + 5x * -1)
2 + 15x = 2 + (3 + -5x)

Combine like terms: 2 + 3 = 5
2 + 15x = 5 + -5x

Solving
2 + 15x = 5 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
2 + 15x + 5x = 5 + -5x + 5x

Combine like terms: 15x + 5x = 20x
2 + 20x = 5 + -5x + 5x

Combine like terms: -5x + 5x = 0
2 + 20x = 5 + 0
2 + 20x = 5

Add '-2' to each side of the equation.
2 + -2 + 20x = 5 + -2

Combine like terms: 2 + -2 = 0
0 + 20x = 5 + -2
20x = 5 + -2

Combine like terms: 5 + -2 = 3
20x = 3

Divide each side by '20'.
x = 0.15

Simplifying
x = 0.15

See similar equations:

| F(x)=4x^2+7x-6 | | 5(2x+1)=3x+19 | | -7x^2+34x+5= | | x+2(80-x)=100-4(25-x) | | 6x/(x^2) | | g^2+4g-32=9 | | 5x=6x-14+12 | | y/7=2/x | | 84/(7) | | 9x/4=15 | | 9x/4=`15 | | 3x+5(2x-12)=5 | | 4x+3y=z | | 8+5x=7x+2 | | -2+10x=8x+1 | | -6*x=36 | | -3(2s-2)-6=-3(7s+3)-4 | | x^3+x^2-42x-291=0 | | 4x+5y+8=0 | | p=3.04+.077y | | 7381=-5/x^6 | | (6x-1)(9x+6)=0 | | x^2-3x-2x-6=0 | | (2x+9)(x-5)=50 | | 2c^2+9z-2=0 | | 7x^2+12x-9=0 | | y=-.13+24.04 | | 4+2+(x-3)=8x+6 | | 7/x=147 | | 0.07x=3.01 | | 15y+28-2(9y+2)= | | 9y+2= |

Equations solver categories